1974
DOI: 10.1136/jcp.27.4.315
|View full text |Cite
|
Sign up to set email alerts
|

Changes in composition of mucin in the mucosa adjacent to carcinoma of the colon as compared with the normal: A biochemical investigation

Abstract: Fifteen surgical specimens from patients with carcinoma of the colon and rectum were studied. Scrapings from normal mucosa distant from the tumour and from macroscopically normal mucosa adjacent to the tumour (`transitional') were used for chemical estimation of hexosamines, sialic acid, and proteins. The presence of hexosamines and sialic acid was confirmed in both normal and transitional mucosa. Transitional mucosa showed increased levels of total hexosamines and sialic acid as compared with the normal and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

1975
1975
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…If this hypothesis is correct, then they may play an important role in the immunological reaction to tumour specific antigens in the control of tumour growth (Baldwin, 1970). In fact, we have found greater amounts of neuraminidase sensitive neuraminic acids in the mucosa around carcinoma in man (Filipe and Cooke, 1974) and they are more abundant in our most invasive tumours (Filipe and Branfoot, 1974). In DMH treated rats we have also observed that the amount of sialomucins present in the focal areas of dysplasia varies during the progress of the experiment, possibly reflecting the immunological status of the host and thus affecting the tumour growth potential.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…If this hypothesis is correct, then they may play an important role in the immunological reaction to tumour specific antigens in the control of tumour growth (Baldwin, 1970). In fact, we have found greater amounts of neuraminidase sensitive neuraminic acids in the mucosa around carcinoma in man (Filipe and Cooke, 1974) and they are more abundant in our most invasive tumours (Filipe and Branfoot, 1974). In DMH treated rats we have also observed that the amount of sialomucins present in the focal areas of dysplasia varies during the progress of the experiment, possibly reflecting the immunological status of the host and thus affecting the tumour growth potential.…”
Section: Discussionmentioning
confidence: 63%
“…The histochemical changes in the composition of the goblet cell mucin consist of an increase in sialomucins as compared with the normal mucosa in which sulphomucins predominate. The higher level of sialic acids is accompanied by a rise in neuraminidase-sensitive sialic acids (Filipe and Cooke, 1974), a feature described in the human foetal gut mucin (Lev and Orlic, 1974).…”
mentioning
confidence: 99%
“…In the present study, multifocal expression of the BGP was observed in the colorectal mucosa adjacent to 'de novo' carcinoma. The BGP foci may be involved in the 'transitional mucosa' (Filipe and Cooke, 1974) as mentioned earlier, because the similar histologic characteristics to transitional mucosa such as crypt distortion and basal cell hyperplasia were observed in the BGP foci. The sites of BGP expression in tubules usually localized in the generative zone, where a carcinoma is supposed to arise from (Ming et al, 1967;Nagayo, 1975;Oohara et al, 1982;Shimada et al, 1984Shimada et al, , 1992Matsuzaki et al, 1998).…”
Section: Discussionmentioning
confidence: 58%
“…These results indicate that the BGP focus may contribute to the carcinogenesis of the 'de novo' carcinoma. Adjacent mucosa around existing carcinoma, the so-called 'transitional mucosa' (Filipe and Cooke, 1974), has been advocated as a distinct entity which is indicative of premalignant changes such as high proliferative activity (Wang et al, 1992) or K-ras mutation (Zhang et al, 1998) in the crypt stem cell. These observations support the contention that a malignant field change exists in transitional mucosa adjacent to a colorectal carcinoma.…”
mentioning
confidence: 99%
“…The concentrations of sialic acid and hexosamines are higher in mucin secreted by transitional mucosa that is immediately adjacent to colon tumor than the mucin secreted by normal mucosa. 36 At colonic pH, sialic acid will remain deprotonated and will carry a negative charge. The free carboxyl group of calcium alginate will also be deprotonated at the said pH and thereby repel the negatively charged sialic acid moieties.…”
Section: In Vitro Mucoadhesive Propertiesmentioning
confidence: 99%